Industrial robot handbook case histories of effective robot use in 70 areas - Miller, Richard Kendall 1946- (Competitive manufacturing series, 1989)
This is the most extensive work ever published on industrial robots. It is essential reading for manufacturing managers and engineers who need to know how and why robots are being used in industry today. This book provides substantial summaries of robot use in seventy applications, including machine tool loading, spot welding, heat-treat furnaces and packaging. For each application, there are discussions on the physical set-up (amplified with photographs and diagrams), pros and cons, costs and more than 200 case histories. This volume also provides information on robotic fundamentals, the robot manufacturing cell, robot project planning and implementation and cost justification. This book should be of interest to manufacturing managers and engineers.